2016
DOI: 10.1073/pnas.1601443113
|View full text |Cite
|
Sign up to set email alerts
|

Preschool is a sensitive period for the influence of maternal support on the trajectory of hippocampal development

Abstract: Building on well-established animal data demonstrating the effects of early maternal support on hippocampal development and adaptive coping, a few longitudinal studies suggest that early caregiver support also impacts human hippocampal development. How caregiving contributes to human hippocampal developmental trajectories, whether there are sensitive periods for these effects, as well as whether related variation in hippocampal development predicts later childhood emotion functioning are of major public health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
113
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 31 publications
4
113
1
Order By: Relevance
“…Maternal support at neither preschool nor school age emerged as a significant predictor of hippocampal volume, a finding consistent with cross-sectional studies showing that variations in maternal influences do not necessarily emerge as main effects in studies of neurodevelopment (2,3). However, the unique, longitudinal approach of Luby et al (1) reveals a compelling association between maternal support and hippocampal growth trajectories: hippocampal volume increased faster with age among subjects with higher levels of maternal support. In addition, hippocampal growth trajectories predicted emotional regulation, an important endophenotype for virtually all common mental disorders.…”
supporting
confidence: 72%
See 4 more Smart Citations
“…Maternal support at neither preschool nor school age emerged as a significant predictor of hippocampal volume, a finding consistent with cross-sectional studies showing that variations in maternal influences do not necessarily emerge as main effects in studies of neurodevelopment (2,3). However, the unique, longitudinal approach of Luby et al (1) reveals a compelling association between maternal support and hippocampal growth trajectories: hippocampal volume increased faster with age among subjects with higher levels of maternal support. In addition, hippocampal growth trajectories predicted emotional regulation, an important endophenotype for virtually all common mental disorders.…”
supporting
confidence: 72%
“…Sensitive periods for environmental signals are also regionally specific, which may explain the discrepancies noted by Luby et al (1) between their findings and those of others groups. For example, the authors note that Lupien et al (3) reported MRI findings with similarly aged subjects (mid-childhood), showing an association between postnatal maternal depression and the volume of the amygdala, but not the hippocampus.…”
Section: Sensitive Periodsmentioning
(Expert classified)
See 3 more Smart Citations